“. I was born in China but I live in Iceland, I'm adopted and I'm proud of it .”: - The bicultural world of adopted children - Elídóttir, Jórunn (Menntavísindasvið Háskóla Íslands, 2016)
Over 600 children have been adopted internationally to Iceland. They come from many different countries, but the largest groups are from India and China. What these children have in common is that they were abandoned by their biological parents and adopted from their country of birth. It is regarded valuable to keep some ties with the country of origin and considered important for the child's ability to understand the processs of adoption and to develop a positive identity rooted in two cultures. The article focuses on the bicultural socialization of adopted children by exploring research and theoretical perspectives to explain and define what we mean when dealing with these issues. The discussion regarding bicultural socialization and adopted children has not been significant in Iceland. Nevertheless, this is an issue that touches most of those who adopt children from other countries than Iceland. When the child seems to have a different racial background than its parents and even siblings, issues related to identity and identifying with others are of matter to the child’s wellbeing. Ethnic and cultural exploration is one path to develop an understanding of how and why these children are different from others, a way to build personal biographies that bring together adoption, race, and national origin (Tessler and Gamache, 2006). The aim of the study introduced in this article was to gain insight into the opinions and attitudes of girls adopted from China on the topic of their connection with China and their origins and their experience of being adoptees from China. The participants, ten girls, seven to nine years old, were sent an electronic questionnaire and asked about various details of their origin and relationship with China. They could also write comments if they liked and add more details to their answers. The results show that issues concerning their country of origin are of great interest to all the girls. Also they regard it as important to keep in touch with other adopted peers, specially other girls ...